Too afraid to go: fears of dignity violations as reasons for non-use of maternal health services in South Sudan - Sumit Kane; Matilda Rial; Maryse Kok; Anthony Matere; Marjolein Dieleman; Jacqueline E. W. Broerse (BMC, 2018)
Abstract Background South Sudan has one of the worst health and maternal health situations in the world. Across South Sudan, while maternal health services at the primary care level are not well developed, even where they exist, many women do not use them. Developing location specific understanding of what hinders women from using services is key to developing and implementing locally appropriate public health interventions. Methods A qualitative study was conducted to gain insight into what hinders women from using maternal health services. Focus group discussions (5) and interviews (44) were conducted with purposefully selected community members and health personnel. A thematic analysis was done to identify key themes. Results While accessibility, affordability, and perceptions (need and quality of care) related barriers to the use of maternal health services exist and are important, women's decisions to use services are also shaped by a variety of social fears. Societal interactions entailed in the process of going to a health facility, interactions with other people, particularly other women on the facility premises, and the care encounters with health workers, are moments where women are afraid of experiencing dignity violations. Women's decisions to step out of their homes to seek maternal health care are the results of a complex trade-off they make or are willing to make between potential threats to their dignity in the various social spaces they need to traverse in the process of seeking care, their views on ownership of and responsibility for the unborn, and the benefits they ascribe to the care available to them. Conclusions Geographical accessibility, affordability, and perceptions related barriers to the use of maternal health services in South Sudan remain; they need to be addressed. Explicit attention also needs to be paid to address social accessibility related barriers; among others, to identify, address and allay the various social fears and fears of dignity violations that may hold women back from using services. Health services should work towards transforming health facilities into social spaces where all women's and citizen's dignity is protected and upheld.